NAVIGATING CONVERGENCE AND DIVERGENCE: A RE-EVALUATION OF INDIA–CANADA BILATERAL TIES IN A CHANGING GLOBAL ORDER - Pooja; Devi, Sunil (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The bilateral relationship between India and Canada has witnessed a dynamic evolution shaped by historical ties, shared democratic values, and mutual economic interests. In recent decades, however, this relationship has been marked by a complex interplay of geopolitical convergence and strategic divergence. This article seeks to critically examine the evolving geopolitical dynamics and bilateral engagements between India and Canada while assessing the geoeconomic potential of their relationship in the context of the 21st century. India and Canada have made concerted efforts to advance a Comprehensive Economic Partnership Agreement (CEPA), envisioned as a Free Trade Agreement (FTA), with commitments aimed at tariff liberalization and reforms to improve the commercial landscape. Despite the presence of certain bilateral frictions, both nations have increasingly demonstrated a willingness to enhance trade cooperation and economic collaboration. Within this context, the present study seeks to assess the extent of geopolitical and geoeconomic convergence and divergence that has influenced New Delhi’s strategic interest in cultivating a more expansive and multifaceted partnership with Ottawa. Furthermore, the paper aims to explore additional factors contributing to the strengthening of multilateral collaboration and cooperation between India and Canada in the contemporary global context.